2004
DOI: 10.1093/humrep/deh201
|View full text |Cite
|
Sign up to set email alerts
|

The effect of osmotic stress on the metaphase II spindle of human oocytes, and the relevance to cryopreservation.

Abstract: Anisosmotic conditions lead to disruption of the MII spindle in human oocytes. Applying this fundamental knowledge to human oocyte cryopreservation should result in increased numbers of cells maintaining viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 63 publications
3
63
1
6
Order By: Relevance
“…This has not been the case with developmental competence of cat oocytes matured in vitro that was severely impacted by exposure to 0.5 M sucrose (~800 mOsm) for 5 min only (Murakami et al, 2004). We suspect that metaphase plate and spindle of cat oocytes likely are highly sensitive to anisosmotic conditions as it has clearly been shown in mature human oocytes (Mullen et al, 2004). Interestingly, exposure of immature oocytes to dehydrating sucrose solutions for 15 min, wherein oocytes did not regain their initial volume unless returned to isotonic conditions, appeared to be more detrimental than exposures to permeating cryoprotectant solutions of similar osmolarity (e.g.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This has not been the case with developmental competence of cat oocytes matured in vitro that was severely impacted by exposure to 0.5 M sucrose (~800 mOsm) for 5 min only (Murakami et al, 2004). We suspect that metaphase plate and spindle of cat oocytes likely are highly sensitive to anisosmotic conditions as it has clearly been shown in mature human oocytes (Mullen et al, 2004). Interestingly, exposure of immature oocytes to dehydrating sucrose solutions for 15 min, wherein oocytes did not regain their initial volume unless returned to isotonic conditions, appeared to be more detrimental than exposures to permeating cryoprotectant solutions of similar osmolarity (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…Another important prerequisite to developing a practical freezing protocol is understanding oocyte tolerance to radical changes in osmolarity that occur during adding and removing cryoprotectant and exposing the gamete to low temperatures (Critser et al, 1997). The resulting changes in cell volume have been shown to have significant effects on oocyte developmental competence in the mouse (Litkouhi et al, 1997), human (Newton et al, 1999;Mullen et al, 2004), cow (Agca et al, 2000), and rhesus monkey (Songsasen et al, 2002). However, no information is available on the impact of osmotic stress on the immature cat oocyte.…”
Section: Introductionmentioning
confidence: 99%
“…Using the experimental data from the present study and osmotic tolerance data from our previous study (65), we have investigated methods to vitrify human oocytes using computer modeling. Our goal in the present work was to develop a method which should ensure ice-free cryopreservation (i.e.…”
Section: Experiments 3: Computer Modeling Toward An Optimal Vitrificatmentioning
confidence: 99%
“…Rhesus macaque oocytes suffered membrane damage after exposure to concentrations of EG at 3 mol/L or higher using a single-step addition and removal (50), although it was not determined if this damage occurred specifically as a result of the volume excursions, or from a chemical effect of the EG, or an interaction between these 2 factors. While it has been shown that human oocytes can tolerate exposure to fairly high concentrations of mono-and disaccharides (up to 1.5 mol/L; equivalent to a reduction in volume to ~35 % of isotonic (57)) as measured by immediate viability using membrane integrity and enzyme activity (83), a reduced tolerance was reported as measured by MII spindle morphology (65). To our knowledge, viability after osmotic stress, as measured by developmental potential, has not been reported for in vivo matured MII human oocytes.…”
Section: Ethylene Glycol Permeability and Its Use For Vitrificationmentioning
confidence: 99%
“…Indeed, cooling oocytes to room temperature for even as little as 10 minutes can cause irreversible damage to the meiotic spindle. Furthermore, chilling oocytes to 0°C in the presence of a CPA appears to exacerbate these abnormalities (Mullen et al, 2004).…”
Section: Cryobiology and Fertility Preservationmentioning
confidence: 99%